2018
DOI: 10.1016/j.genrep.2018.03.008
|View full text |Cite|
|
Sign up to set email alerts
|

Blockade of vascular endothelial growth factor receptor-1 (Flt-1), reveals a novel analgesic for osteoarthritis-induced joint pain

Abstract: Osteoarthritis (OA) is a painful and debilitating disease. A striking feature of OA is the dramatic increase in vascular endothelial growth factor (VEGF) levels and in new blood vessel formation in the joints, both of which correlate with the severity of OA pain. Our aim was to determine whether anti-VEGF monoclonal antibodies (mAbs) – MF-1 (mAb to VEGFR1) and DC101 (mAb to VEGFR2) – can reduce OA pain and can do so by targeting VEGF signaling pathways such as Flt-1 (VEGFR1) and Flk-1 (VEGFR2). After IACUC app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 22 publications
(66 reference statements)
0
34
0
Order By: Relevance
“…For example, NGF is a well‐known potent inducer of VEGF and VEGF strongly arguments the expression of NGF. For instance, the NGF/TrkA axis highly stimulates VEGFR‐1 expression in the DRG sensory neurons (Das et al, ). VEGF is capable of directly modulating the excitability of primary sensory neurons (Selvaraj et al, ); it is likely that stimulation of one of these factors: either NGF or VEGF signaling may be sufficient enough to trigger and develop back pain sensation in the injured discs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, NGF is a well‐known potent inducer of VEGF and VEGF strongly arguments the expression of NGF. For instance, the NGF/TrkA axis highly stimulates VEGFR‐1 expression in the DRG sensory neurons (Das et al, ). VEGF is capable of directly modulating the excitability of primary sensory neurons (Selvaraj et al, ); it is likely that stimulation of one of these factors: either NGF or VEGF signaling may be sufficient enough to trigger and develop back pain sensation in the injured discs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Selvaraj et al (2015) demonstrated that VEGFR-1/Flt-1 could directly regulate the excitability of sensory neurons and the expression of neuropeptides associated with pain in the dorsal root ganglia (DRG). More recently, Das et al (2018) showed the distinct role of VEGFR-1, but not VEGFR-2, in knee OA pain transmission. Therefore, we hypothesize that VEGFR-1 contributes to the nociceptive pain signal transduction during intervertebral disc (IVD) degeneration.…”
Section: Introductionmentioning
confidence: 99%
“… 77 Notably, systemic anti-Flt-1 antibody treatment reversed mechanical and thermal hyperalgesia. 77 In a mouse knee OA model, IT inhibition of Flt-1 reduced mechanical hyperalgesia, 21 indicating a CNS role of Flt-1 in pain transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In the knee OA, mAbs have shown promising results on mice models and in vitro studies. Targeting of the VEGF monoclonal antibody, including MF-1 (mAb to VEGFR1) and DC101 (mAb to VEGFR2), showed modulatory effects in OA knee pain in mice when applied intraarticularly [ 241 ]. A potential therapeutic option for treating chronic pain, in patients with symptomatic knee OA, could be Tanezumab, a mAb that blocks the Nerve Growth Factor (NGF) from activating Tropomyosin-receptor-kinase (Trk) receptors on nociceptive neurons [ 242 ].…”
Section: Future Strategies For Oa Managementmentioning
confidence: 99%